Pengaruh Brand Ambassador terhadap Niat Beli BTS Meal Kelapa Gading Jakarta Utara dengan Viral Marketing sebagai Variabel Mediasi - Wulandary, Anggie Fitriyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
A brand ambassador is someone who has an appeal to consumers and can influence consumers to buy the product. This brand ambassador has been widely used by business people, one of which is McDonald's, McDonald's makes BTS as brand ambassadors. Basic is eWoM theory which states that viral marketing is one part of e-WoM and is a mediating variable from brand ambassadors that affects purchase intention. Respondents were those who had ever purchased BTS Meal in Kelapa Gading, North Jakarta. The sampling technique used is non-probability sampling using Judgmental Sampling, with a sample of 113 respondents. The data were analyzed using multiple linear regression and path analysis, and Sobel test, with SPSS and Online Mediation Calculator as tools. This study concludes that brand ambassadors, viral marketing are confirmed as the determinant of purchase intention of BTS Meal. Further research is suggested to conduct the study in different context.